Azilsartan as a Potent Antihypertensive Drug with Possible Pleiotropic Cardiometabolic Effects: A Review Study - Georgiopoulos, Georgios; Katsi, Vasiliki; Oikonomou, Dimitrios; Vamvakou, Georgia; Koutli, Evangelia; Laina, Aggeliki; Tsioufis, Constantinos; Nihoyannopoulos, Petros; Tousoulis, Dimitrios (Frontiers in Pharmacology, 2016)
Background: Hypertension related cardiovascular (CV) complications could be amplified by the presence of metabolic co-morbidities. Azilsartan medoxomil (AZL-M) is the eighth approved member of angiotensin II receptor blockers (ARBs), a drug class of high priority in the management of hypertensive subjects with diabetes mellitus type II (DMII). Methods: Under this prism, we performed a systematic review of the literature for all relevant articles in order to evaluate the efficacy, safety and possible clinical role of AZL-M in hypertensive diabetic patients. Results: AZL-M was found to be more effective in terms of reducing indices of blood pressure over alternative ARBs or angiotensin-converting enzyme inhibitors with minimal side effects. Preclinical studies have established pleiotropic effects for AZL-M beyond its primary antihypertensive role through differential gene expression, up-regulation of membrane receptors and favorable effect on selective intracellular biochemical and pro-atherosclerotic pathways. Conclusion: Indirect but accumulating evidence from recent literature supports the efficacy and safety of AZL-M among diabetic patients. However, no clinical data exist to date that evince a beneficial role of AZL-M in patients with metabolic disorders on top of its antihypertensive effect. Further clinical studies are warranted to assess the pleiotropic cardiometabolic benefits of AZL-M that are derived from preclinical research.